Serological and molecular epidemiology of Japanese Encephalitis in Zhejiang, China, 2015-2018. - Xuan Deng; Ju-Ying Yan; Han-Qing He; Rui Yan; Yi Sun; Xue-Wen Tang; Yang Zhou; Jun-Hang Pan; Hai-Yan Mao; Yan-Jun Zhang; Hua-Kun Lv (Public Library of Science (PLoS), 2020)
Background Shifts have occurred in the epidemiological characteristics of Japanese encephalitis (JE), extending from the molecular level to the population level. The aim of this study was to investigate the seroprevalence of JE neutralizing antibodies in healthy populations from different age groups in Zhejiang Province, and to conduct mosquito monitoring to evaluate the infection rate of Japanese encephalitis virus (JEV) among vectors, as well as the molecular characteristics of the E gene of isolated JEV strains. Methodology/principal findings A total of 1190 sera samples were screened by a microseroneutralization test, including 429 infants (28d-11m) and 761 participants (2y-82y). For those under 1 year old, the geometric mean titers (GMTs) of the JE neutralizing antibody was 9.49 at birth and significantly declined as the age of month increased (r = -0.225, P<0.001). For those above 1-year old, seropositive proportions were higher in subjects aged 1-3 years old as well as ≥25 years old (65%-75%), and relatively lower in subjects aged between 4-25 years old (22%-55%). Four or more years after the 2nd dose of JEV-L (first dose administered at 8 months and the second at 2 years of age), the seropositive proportion decreased to 32.5%, and GMTs decreased to 8.08. A total of 87,201 mosquitoes were collected from livestock sheds in 6 surveillance sites during 2015-2018, from which 139 E gene sequences were successfully amplified. The annual infection rate according to bias-corrected maximum likelihood estimation of JEV in Culex tritaeniorhynchus was 1.56, 2.36, 5.65 and 1.77 per 1000, respectively. JEV strains isolated during 2015-2018 all belonged to Genotype I. The E gene of amplified 139 samples differed from the JEV-L vaccine strain at fourteen amino acid residues, including the eight key residues related to virulence and virus attenuation. No divergence was observed at the sites related to antigenicity. Conclusions/significance Zhejiang Province was at a high risk of JE exposure due to relatively lower neutralizing antibody levels among the younger-aged population and higher infection rates of JEV in mosquitoes. Continuous, timely and full coverage of JE vaccination are essential, as well as the separation of human living areas and livestock shed areas. In addition, annual mosquito surveillance and periodic antibody level monitoring are important for providing evidence for improvement in JE vaccines and immunization schedules.